Mental but no bio-physiological long-term habituation to repeated social stress: A study on soldiers and the influence of mission abroad - Tanja Maier; Manuela Rappel; Dae-Sup Rhee; Sebastian Brill; Julia Maderner; Friederike Pijahn; Harald Gündel; Peter Radermacher; Benedikt Friemert; Horst-Peter Becker; Christiane Waller; Christiane Waller (Frontiers in Psychiatry, 2022)
Soldiers regularly participate in missions abroad and subjectively adapt to this situation. However, they have an increased lifetime cardiovascular risk compared to other occupational groups. To test the hypothesis that foreign deployment results in different stress habituation patterns, we investigated long-term psychological and bio-physiological stress responses to a repeated social stress task in healthy soldiers with and without foreign deployment. Ninety-one female and male soldiers from the BEST study (German armed forces deployment and stress) participated three times in the Trier Social Stress Test for groups (TSST-G) prior to, 6–8 weeks after and 1 year after the mission abroad and were compared to a control group without foreign deployment during the study period. They completed the State-Trait-Anxiety Inventory scale (STAI), the Primary Appraisal Secondary Appraisal questionnaire (PASA) and the Multidimensional Mood State Questionnaire (MDBF). Salivary cortisol and α-amylase, blood pressure, heart rate and heart rate variability were determined. Soldiers showed mental habituation over the three times with a significant decrease after the TSST-G in anxiousness (STAI) and cognitive stress appraisal (PASA), they were calmer and reported better mood (MDBF). Prior to the social stress part, the mood (MDBF) declined significantly. None of the biological and physiological markers showed any adaptation to the TSST-G. Mission abroad did not significantly influence any measured psychobiological marker when compared to soldiers without foreign deployment. Foreign deployment does not result in alterations in psychobiological social stress response patterns over 1 year after mission abroad which indicates that adaptation to acute social stress is highly maintained in healthy soldiers. The discrepancy between subjective perception and objective stress response has numerous clinical implications and should receive more attention.